Factors impacting the efficacy of venlafaxine extended release 75–225 mg/day in patients with major depressive disorder: exploratory post hoc subgroup analyses of a randomized, double-blind, placebo-controlled study in Japan - Watanabe Y (Dove Medical Press, 2018)
Yoshinori Watanabe,1 Yuko Asami,2 Yoko Hirano,2 Kazuhiko Kuribayashi,3 Rio Itamura,4 Takayuki Imaeda4 1Himorogi Psychiatric Institute, Tokyo, Japan; 2Medical Affairs, Pfizer Essential Health, Pfizer Japan Inc., Tokyo, Japan; 3Clinical Statistics, Pfizer Japan Inc., Tokyo, Japan; 4Clinical Research, Pfizer Japan Inc., Tokyo, Japan Purpose: To explore the potential factors impacting the efficacy of venlafaxine extended release (ER) and treatment differences between 75 mg/day and 75–225 mg/day dose in patients with major depressive disorder (MDD). Methods: We performed exploratory post hoc subgroup analyses of a randomized, double-blind, placebo-controlled study conducted in Japan. A total of 538 outpatients aged 20 years or older with a primary diagnosis of MDD who experienced single or recurrent episodes were randomized into three groups: fixed-dose, flexible-dose, or placebo. Venlafaxine ER was initiated at 37.5 mg/day and titrated to 75 mg/day for both fixed-dose and flexible-dose group, and to 225 mg/day for flexible-dose group (if well tolerated). Efficacy endpoints were changes from baseline at Week 8 using the Hamilton Rating Scale for Depression–17 items (HAM-D17) total score, Hamilton Rating Scale for Depression–6 items score, and Montgomery–Asberg Depression Rating Scale total score. The following factors were considered in the subgroup analyses: sex, age, HAM-D17 total score at baseline, duration of MDD, duration of current depressive episode, history of previous depressive episodes, history of previous medications for MDD, and CYP2D6 phenotype. For each subgroup, an analysis of covariance model was fitted and the adjusted mean of the treatment effect and corresponding 95% CI were computed. Due to the exploratory nature of the investigation, no statistical hypothesis testing was used. Results: Venlafaxine ER improved symptoms of MDD compared with placebo in most subgroups. The subgroup with a long duration of MDD (>22 months) consistently showed greater treatment benefits in the flexible-dose group than in the fixed-dose group. Conclusion: These results suggest that a greater treatment response to venlafaxine ER (up to 225 mg/day) can be seen in patients with a longer duration of MDD. Further investigations are needed to identify additional factors impacting the efficacy of venlafaxine ER. Keywords: venlafaxine, Hamilton Rating Scale for Depression, HAM-D, subgroup, major depressive disorder, MDD, Montgomery–Asberg Depression Rating Scale, MADRS